Intracystic papillary carcinoma of the breast in males: Three case reports. Issue 25 (19th June 2020) - Luo, Hua; Meng, Kexin; He, Junling; Hu, Zujian; Yang, Ouou; Lan, Tian; Su, Kunlun; Yang, Huifen; Zhan, Chenni; Xu, Haibin
Abstract: Rationale: Intracystic papillary breast carcinoma is extremely rare in males with a favorable prognosis. Clinical and mammographic manifestations of IPC are not specific, and no consensus has been reached on its management. Patient concerns: Three cases of IPC of the breast in male patients who underwent surgery are presented. In each patient, clinical manifestations, radiological appearance, surgical procedures, pathological diagnosis, and prognosis were investigated. Diagnosis: Ultrasonography showed a complex mass with cystic and nodular solid components in 2 patients and a solid hypoechoic mass in the other 1. Contrast-enhanced ultrasonography(CEUS) was performed for 1 patient demonstrated a solid component of the characteristic enhancement patterns. The final diagnosis of IPC was made after an excisional biopsy. Interventions: A mastectomy with sentinel lymph node mapping was carried out in 2 patients, and it was negative for metastatic disease. The third patient received a mastectomy without an investigation of the axillary lymph node status. Outcomes: All the patients are disease-free during a median follow-up of 67 months (range, 13–120) months. Lessons: It is difficult to diagnose IPC of the male breast before surgery, excisional biopsy is necessary. CEUS can be useful to diagnose IPC in male patients in the preoperative evaluation. Sentinel node biopsy may be considered in patients with IPC associated with DCIS or invasive carcinoma.